Early colonialism and the Mi'kmaq: A context for re-thinking history of religion. - Reid, Jennifer. (University of Ottawa (Canada), 1992)
This paper considers the religious meaning of earliest contact between Europeans and North American indigenous peoples as it focuses upon the meeting of the French and the Mi'kmaq in Acadia during the sixteenth and early seventeenth centuries, and the trade in commodities which initiated and maintained their cultural interaction during this period. Religion in this context is defined as the fundamental orientation of the human which is achieved through reciprocity; in other words, it is the process by which the human being arrives at a notion of meaning in the world and it is realized through exchanges in materiality. This definition provides a locus for the discussion of two issues; first, what is referred to a the 'problem' of the modern study of religion; and second, the problematic nature of the meaning of colonialism itself.
Keywords: Religion, History of.